PERCUTANEOUS ETHANOL INJECTION IN BENIGN NONTOXIC MULTINODULAR GOITER - Lorda, Lázaro (2023)
Introduction: Benign non-toxic multinodular goiter is one of the most common endocrine diseases that affect the current population, and it is, in turn, the endocrine disease that most frequently requires surgical intervention. Objective: To show the results of percutaneous ethanol injection in the treatment of patients with benign non-toxic multinodular goiter in the short and medium term. Methods: A prospective longitudinal study was conducted in patients with benign nontoxic multinodular goiter treated with percutaneous ethanol injection. The categorical variables were described by absolute frequencies and percentages, and for the numerical variables the mean, standard deviation, as well as the minimum and maximum values were calculated. To evaluate the changes between the initial and final volumes of the nodules, the Student's t-test for related samples was used. Results: The mean percentage reduction in the volume of the nodules was 48.23 ± 9.55; 58.05 ± 11.79 and 69.49 ± 13.11; a month, 3 months and 6 months after the treatment, respectively. Clinical success was complete in 67.3%, 75.5%, and 87.8% of the patients, at 1, 3, and 6 months of post-treatment follow-up, respectively. There were no complications. Conclusions: Percutaneous ethanol injection is an alternative to surgery for the treatment of patients with benign non-toxic multinodular goiter, it is safe, effective, with transient adverse effects and very rare complications in the short and medium term.